2011
DOI: 10.1039/c0cp01818j
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state electropolymerization and doping of triphenylamine as a route for electroactive thin films

Abstract: Solid-state electropolymerization could be a way to produce organic semiconductors with potential application as Hole Transporting Materials (HTMs) in hybrid organic-inorganic devices. Thereby, thin solid films of triphenylamine (TPA) deposited by spin coating on conducting glass substrates have been electrochemically treated by performing multiple voltammetric cycles between -0.4 V and 1.0 V vs. Ag/AgCl in a 0.5 M sodium perchlorate aqueous electrolyte. Subsequent characterization by means of in situ UV-Vis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 44 publications
4
20
0
Order By: Relevance
“…This type of behavior has been previously ascribed to an oxidative solid-state electrochemical cross-linking. [15][16][17]34] In agreement, it has been previously reported that TTPA can be electrochemically polymerized from solution, generating an amorphous conducting polymer. [29][30][31] After about 40 cycles, an apparent stable response is observed: the oxidation process starts at 0.45 V in both films, while the corresponding reduction peak is observed at about 0.55 (TTPA) and 0.61 V (TSePA).…”
supporting
confidence: 80%
See 1 more Smart Citation
“…This type of behavior has been previously ascribed to an oxidative solid-state electrochemical cross-linking. [15][16][17]34] In agreement, it has been previously reported that TTPA can be electrochemically polymerized from solution, generating an amorphous conducting polymer. [29][30][31] After about 40 cycles, an apparent stable response is observed: the oxidation process starts at 0.45 V in both films, while the corresponding reduction peak is observed at about 0.55 (TTPA) and 0.61 V (TSePA).…”
supporting
confidence: 80%
“…The original spectra of TTPA and TSePA are characterized by the presence of a broad band at l < 450 nm, which can be ascribed to the onset of the p-p* transition. This band is displaced toward longer wavelengths compared with that of the triphenylamine molecule [34] due to the presence of thiophene and selenophene units. [35] After voltammetric cycling, a new band develops in both films, the onset of which is located at around 500 nm for TTPA and 550 nm for TSePA.…”
mentioning
confidence: 92%
“…5 nm, as seen for instance in Figure 11(a) for complex 2 electrodeposited at 250 mV/s scan rate. For lower scan rates, AFM images reveal a higher roughness of the film surface (R RMS = 22 nm) and show a cauliflower-like texture similar in features to films of TPA obtained through solid-state electropolymerization 39 (Figure 11b). …”
Section: Resultsmentioning
confidence: 86%
“…Importantly, the oxidation onset is located around 0.1 V less positive than in the case of QT12 and, therefore, the valence band for pTPA would be located at À5.43 eV, that is, 0.1 eV less negative than the QT12 HOMO level. The UV-vis spectra given for pTPA in our previous report 31 QT12 (in the ESIw) allow us to estimate the HOMO-LUMO difference as 3.26 and 2.76 eV, respectively. On the other hand, the conduction band of TiO 2 (at the isoelectric point) has been located at À4.2 eV.…”
Section: Resultsmentioning
confidence: 99%